Indications and Outcomes of Emergency Obstetric Hysterectomy at Tertiary Care Hospital - Sidra Farooq, Zubaida Khanum Wazir, Noreen Tahir, Shermeen Kousar, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To analyze the indications and outcomes of the emergency obstetric hysterectomy at tertiary care hospital. Study Design: Descriptive cross-sectional study Place and Duration: Conducted for the period of six months from December 2022 to May 2023, at the Department of Obstetrics and Gynecology at Gulnawaz Teaching Hospital Bannu and Al-Nafees Medical college and Hospital Islamabad. Materials and method: A total of 88 females were selected through a purposive sampling technique and the females were from 20- 40 years of age. Informed consent was obtained from each participant who was willing, in addition, they were assured that their privacy and confidentiality will be maintained. The data was collected through a well-structured questionnaire from each participant. All the data were analyzed properly by using the latest version of SPSS 24. Results: There were 88 female’s patients who underwent emergency obstetric hysterectomy. 23.86 % and 30.68 % of the patients were aged 31-35 and 36-40 years, and most of them were multiparous. 26. 13 % of the cases were with uterus rupture, while 21.59 % of the patients were presented with adhered placenta, which was mainly associated with a previous history of cesarean section. In addition, 19.31 % of the cases were presented with atonic postpartum hemorrhage. 14.7 % of the individual have uterine atony. 39.77 % of the patients had developed anemia after the surgery, while 21.59 % of patients needed a vasopressor, along with that, 7.95 % of the patients were admitted to the intensive care unit, and 3.40 % were reopened (repeated laparotomy). Conclusion: The present study concluded that cesarean sections were the main contributing factors to emergency obstetric hysterectomy that leads to placental abnormalities, moreover, uterine rupture and adherent placenta as the main causes of EOH. Therefore, the frequency of cesarean sections needs to be reduced and more care is needed for the patients during and after the surgeries to minimize the complications. Keywords: Laparotomy, placental abnormality, anemia, cesarean section